Research on the influential characteristics of asymmetric wind fields on typhoon waves - Wu, Yan; Dou, Shentang; Fan, Yaoshen; Yu, Shoubing; Dai, Weiqi (Frontiers in Marine Science, 2023)
The East China Sea is an ocean region with frequent typhoons; typhoons are also the main reason for inducing typhoon waves. The complexity of typhoon waves is closely related to the complexity of typhoon wind field. In previous studies, symmetrical wind field models or superimposed wind field models were usually used to simulate typhoon waves. However, the actual wind fields are asymmetric, and the asymmetry is affected by many factors. Therefore, three wind field models, i.e., circular symmetrical wind field model, superimposed wind field model, and asymmetric wind field model, are used to simulate the wind field of Typhoon Muifa that moved through the East China Sea. Moreover, the abovementioned wind field models are used to drive the third-generation wave model SWAN to simulate the wave field and wave spectrum of Typhoon Muifa to evaluate the effect of the asymmetry of the typhoon on its wave and internal energy distribution characteristics. Studies show that the values generated by the asymmetric wind field model are most consistent with the actual measurement data. This is especially the case if the typhoon center is closer to the station. The accuracy of the typhoon waves simulated using the asymmetric wind field model is better than that of the other two wind field models. The asymmetric wind field can reflect the asymmetric characteristics of the typhoon well. The substantial wave heights on the right side of typhoon’s path are substantially higher than those on the left side of path. Additionally, the maximum wave spectral density and total energy of waves as simulated by the asymmetric wind field are both larger than those of the other two wind field models. Thus, the asymmetric wind field model is more suitable for the numerical simulation of typhoon waves in the East China Sea.